X+10=7x-26

Simple and best practice solution for X+10=7x-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+10=7x-26 equation:


Simplifying
X + 10 = 7x + -26

Reorder the terms:
10 + X = 7x + -26

Reorder the terms:
10 + X = -26 + 7x

Solving
10 + X = -26 + 7x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + X = -26 + -10 + 7x

Combine like terms: 10 + -10 = 0
0 + X = -26 + -10 + 7x
X = -26 + -10 + 7x

Combine like terms: -26 + -10 = -36
X = -36 + 7x

Simplifying
X = -36 + 7x

See similar equations:

| Since=0.48 | | 2x^2-16+20=0 | | 10=z/6-2 | | 3(x-1)+3-2x=4 | | 9x^2+7=8 | | (1/3)^3.14*4*3^2 | | 15/x=x-2 | | 8f+9=15 | | 5c+1=-1+6x | | 3(y-6)-5y= | | 8+5x=-4x+80 | | (4x+1)(x-6)=0 | | 5c(c+7)= | | am^2+6m+1=0 | | y-5x=-25 | | ln(x)=300000 | | 0=x^2-5.6x+4.6 | | (1/3)3.14(3^2)4 | | 5x+10=6y+30 | | 3/7(-1/8) | | 1/3^5=3^-5 | | Ln(3x+7)=4.36 | | y-3+6=9 | | t-6-3=11 | | a=h(a+b)2forh | | 2y=-3(x-5) | | 9-(5x+8)=10x-17 | | a-3+2=10 | | 4(8-s)+6=2 | | 4x+2y=104 | | 4-x/10=8 | | 3x+15=8x-20 |

Equations solver categories